USE OF DISTANCE LEARNING TECHNOLOGIES IN THE MODERN EDUCATIONAL PROCESS - HEVLYCH, Ivan; NESKORODIEVA Тetiana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Distance learning is currently a common practice in the organization of the educational process. For this, various software products tested during the coronavirus pandemic in 2020-2021 and martial law in Ukraine in 2022 are used. At the same time, studies of the use of modern distance technologies in the educational process are devoted to conceptual aspects of the organization of education or are based on various software products. All of the above requires the definition of effective remote technologies for solving various tasks of educational activities in domestic higher educational institutions. The purpose of the work is to study the software products used in the educational process of Vasyl’ Stus Donetsk National University, from the point of view of optimization of scientific and educational activities. The article summarizes the practice of using IT technologies at Vasyl’ Stus Donetsk National University since its relocation in 2014. This made it possible to determine the advantages and disadvantages of modern use for the organization of the educational process, joint activities, including scientific and educational, platform Moodle, IT services Microsoft Office-365, as well as highlight the most popular services in the academic space. It is noted that Google services today are a strong competitor to Microsoft’s IT services, in particular, due to their quality, variety and free of charge. It was established that the availability of practical skills for working in Google Classroom among students requires mastery of this tool for teachers of higher educational institutions in order to make a further decision regarding the effectiveness of solving educational tasks. According to the results of the research, the necessity of combining various IT services, as well as constant training of the participants of the educational process in the skills of their use, was established. The direction of further research is the problem of developing training courses using various distance learning IT services.